Real-time PCR assay in differentiating Entamoeba histolytica, Entamoeba dispar, and Entamoeba moshkovskii infections in Orang Asli settlements in Malaysia - Lau, Yee Ling; Anthony, C.; Fakhrurrazi, S.A.; Jamaiah, I.; Ithoi, Init; Mahmud, Rohela (BMC, 2013)
Background: Amebiasis caused by Entamoeba histolytica is the third leading cause of death worldwide. This pathogenic amoeba is morphologically indistinguishable from E. dispar and E. moshkovskii, the non-pathogenic species. Polymerase chain reaction is the current method of choice approved by World Health Organization. Real-time PCR is another attractive molecular method for diagnosis of infectious diseases as post-PCR analyses are eliminated and turnaround times are shorter. The present work aimed to compare the results of Entamoeba species identification using the real-time assay against the established nested PCR method. Methods: In this study, a total of 334 human faecal samples were collected from different Orang Asli settlements. Faecal samples were processed by direct wet smear and formalin ethyl acetate concentration methods followed by iodine staining and was microscopically examined for Entamoeba species and other intestinal parasites. Microscopically positive samples were then subject to nested PCR and real-time PCR. Results: The overall prevalence of Entamoeba infection was 19.5 (65/334). SK Posh Piah recorded highest Entamoeba prevalence (63.3) while Kampung Kemensah had the lowest prevalence (3.7) of Entamoeba. Microscopically positive samples were then tested by real-time PCR and nested PCR for the presence of Entamoeba histolytica, Entamoeba dispar, and Entamoeba moshkovskii infection. Real-time PCR showed higher Entamoeba detection (86.2) compared to nested PCR (80), although the McNemar test value showed no significant difference between the two methods (p = 0.221). Conclusions: This study is the first in Malaysia to report the use of real-time PCR in identifying and differentiating the three Entamoeba infections. It is also proven to be more effective compared to the conventional nested PCR molecular method.